Use of restoration plantings to enhance bird seed dispersal at the roadside: failures and prospects - Torres, Rocío de; Jiménez, María Dolores; Ramírez, Álvaro; Mola, Ignacio; A. Casado, Miguel; Balaguer, Luis (Journal of Environmental Engineering and Landscape Management, 2015)
Plantings are commonly used in roadside reclamation for ornamental purposes and for increasing slope stability and road safety. However, the role of these plantings in restoring ecological processes, such as seed dispersal, has received little attention. We carried out a study to assess the potential role of plantings on roadside embankments to attract frugivorous birds and to enhance seed dispersal mediated by birds from the surrounding landscape. We examined: (1) bird species richness and abundance; (2) patterns of avian spatial distribution within embankments and (3) seed dispersal mediated by birds. Bird richness and abundance did not differ between embankments with and without plantings. However, birds were not distributed randomly within embankments, with levels of species richness and abundance for facultative frugivorous between 4.8–8 times higher in areas closer to plantings. An analysis of bird droppings showed that birds only dispersed seeds of the planted species since no seeds of woody plants from matrices were detected. These results suggest that plantings acted as selective bird attractors, providing food and perches for frugivorous species. Nevertheless, the scarcity of seed-dispersing birds in the surrounding agricultural landscape prevented plantings from enhancing seed dispersal and connectivity to adjacent habitat.